Enhancing Knowledge, Attitudes, and Motivation in Stunting Prevention by Community-Based Education - Handayani, Lina; Trisnowati, Heni; Novianti, Tria Nisa; Fitriani, Isah; Vergawita, Tania; Suryana, Aufatcha Ayutya; Nasir, Ardiansyah Jumaedi; Eka Saputri, Melly (Jurnal Ilmiah Kesehatan Masyarakat : Media Komunikasi Komunitas Kesehatan Masyarakat, 2025)
Abstract Background: Stunting is a global public health problem that can impair children's physical and cognitive development. In Indonesia, although the prevalence of stunting has decreased, it is still relatively high. Adolescents, especially adolescent girls, play an essential role in stunting prevention, as their knowledge, attitudes, and motivation can influence the health of future generations. Community-based education, such as Karang Taruna youth groups at the village or kelurahan level, using audiovisual media, is considered adequate for increasing adolescents' understanding and awareness of stunting. Method: This study used a quasi-experimental method with a one-group pretest-posttest design. The sample was 33 adolescents in Sumberan Hamlet, Sleman, Yogyakarta. The intervention was stunting prevention education using audiovisual media delivered in one one-hour session in October 2024. Data were collected through questionnaires to measure knowledge, attitudes, and motivation which were standardized and analyzed using the Wilcoxon Signed Rank test. Result: This study showed a significant increase in adolescents' knowledge with a mean difference between pre-test and post-test of 9.26 (p=0.001) and in attitude with a mean difference of 2.33 (p=0.003) after the intervention. However, adolescents' motivation did not increase significantly, with a mean difference between pre-test and post-test of only 0.70 (p=0.274). Conclusion: Community-based education using audiovisual media effectively improves adolescents' knowledge and attitudes about stunting.